Taking Command : The Autobiography - Richards, David Gen. (London Headling Publishing, 2014)
The outspoken autobiography of one of Britain's best known, and respected, Generals
Include Color Illustration and Index
Keywords: Great Britain -- Richards, David (David Julian), 1952-